2023
DOI: 10.3390/ijms24021615
|View full text |Cite
|
Sign up to set email alerts
|

A Promising Strategy to Treat Neurodegenerative Diseases by SIRT3 Activation

Abstract: SIRT3, the primary mitochondrial deacetylase, regulates the functions of mitochondrial proteins including metabolic enzymes and respiratory chain components. Although SIRT3’s functions in peripheral tissues are well established, the significance of its downregulation in neurodegenerative diseases is beginning to emerge. SIRT3 plays a key role in brain energy metabolism and provides substrate flexibility to neurons. It also facilitates metabolic coupling between fuel substrate-producing tissues and fuel-consumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 189 publications
0
3
0
Order By: Relevance
“…It can prevent or alleviate mitochondrial dysfunction and has neuroprotective effects [31]. Modulation of SIRT3 activity now represents a powerful strategy for treating neurodegenerative diseases [55]. A previous study showed that increasing NAD + levels upregulates SIRT3 activity [56].…”
Section: Discussionmentioning
confidence: 99%
“…It can prevent or alleviate mitochondrial dysfunction and has neuroprotective effects [31]. Modulation of SIRT3 activity now represents a powerful strategy for treating neurodegenerative diseases [55]. A previous study showed that increasing NAD + levels upregulates SIRT3 activity [56].…”
Section: Discussionmentioning
confidence: 99%
“…Neurodegenerative diseases occur with ageing and many elderly people are more and more exposed. It affects the neurology system, then conducts to brain cell death [1]. The main symptoms are characterized by loss of autonomy, depression, anxiety, progressive memory loss, language disability, bradykinesia and muscular rigidity… [2].…”
Section: Introductionmentioning
confidence: 99%
“…It is an NAD+-dependent deacetylase that finely regulates the cellular energetic homeostasis and oxidative stress response. 14 In addition to its role in exercise, 15 aging 16 and treating bone, 17,18 cardiovascular 19 and neurodegenerative diseases, 20,21 SIRT3 has positive or negative effects on the occurrence and development of various cancers. 22,23 For instance, SIRT3 deacetylates cyclin E2 to inhibit the growth of hepatocellular carcinoma, 24 and overexpression of SIRT3 can induce ovarian cancer cell death, 25 etc.…”
mentioning
confidence: 99%